FRI0251 Prevalence of gout and the use of urate lowering agents in us general population nhanes 2007–2016. (12th June 2018) - Cheung, T.T.; Tsoi, M.F.; Cheung, B.M.Y.; Lau, W.C.S.
Abstract : Background: The prevalence of gout has been increasing worldwide. Previous study using National Health and Nutritional Examination Survey (NHANES) showed an increase of 1.2% in the prevalence of gout in the US general population from 1988 to 2007. However, it is unknown if this trend continued over the past decades. Therefore, we would like to determine the prevalence of gout in the US general population using NHANES 2007 to 2016. In addition, the use of urate lowering agents among patients with gout was analysed. Objectives: To estimate the prevalence of gout and the use of urate lowering agents using the National Health and Nutritional Examination Survey from 2007 to 2016 Methods: Adult participants in NHANES 2007–2016 were included in the analysis. NHANES is a continuous national survey conducted by the US Centres for Disease Control and Prevention and is designed to evaluate the health and nutritional status of adults and children in the US. They are based on a representative sample of the non-institutionalised US civilian population. Each participant represents approximately 50000 Americans. The primary outcome was self-reported gout. Factors associated with gout, such as body weight, drinking habit, history of chronic kidney disease, use of aspirin and thiazide diuretics were evaluated. Prescriptions of allopurinol, febuxostat or probenacid were retrieved from the NHANES dataset to evaluate the use of urate lowering agents among patients with gout. Results were analysed using SPSS complex sample module version 22. Multiple regression was used to analyse the difference in prevalence of gout and utilisation of urate lowering agents. Results: 23482 adults participants were included in the analysis. There was no further increase in the prevalence of gout in the general US population. The prevalence was 3.82% and 3.84% in NHANES 2007–2010 and 2011–2016, respectively (p=0.966). Although there is a decreasing trend in the serum urate levels among patients with gout, the utilisation of urate lowering agents remained low. Only 28.2% and 29.4% of patients with gout were prescribed urate lowering agents in 2007–2010 and 2011–2014, respectively. Among patients with gout, history of chronic kidney disease and use of thiazide diuretics are the most significant negative predictors for achieving the therapeutic target of SUV <6 mg/dL (Odds ratio of 0.23 and 0.41, respectively). Use of aspirin was not a significant predictor for treatment failure. Conclusions: The prevalence of gout in the US general population has not increased over the past 10 years. Although the use of urate lowering agents among patients with gout remained low, the percentage of patients with gout achieving the therapeutic target has increased over the past 10 years. History of chronic kidney disease and use of thiazide diuretics are the most significant negative predictors for treatment success. Disclosure of Interest: None declared